Ruru Raag - Natasha Sharma (Tulika Publisher, 2013)
Do roosters sing ragas? This one does but like all true artistes discovers it after a lot of struggle! Every time he opens his mouth he has a new tune but not the kukaroo-kuroo of the other roosters. His friends skip and stretch, stamp and roll and try to teach him.
Grade - 2